Crisis in Bilateral Economic Cooperation between Russia and Spain - K. A. Nikulin (Ассоциация независимых экспертов «Центр изучения кризисного общества» (in English: Association for independent experts “Center for Crisis Society Studies”), 2021)
The article examines the dynamics and features of the trade and economic partnership between Spain and Russia from 2014 to the present, considering the latest challenges. The once promising trajectory of the development of bilateral trade and mutual investment has undergone significant tests: in addition to the sanctions pressure of the collective West countries, the situation has been complicated by the global crisis in the world economy, significant changes in world markets for goods and services, and the COVID-19 pandemic. In these conditions, the study of indicators of Russian-Spanish trade and economic interaction is of interest both from the point of view of forming a forecast for the development of bilateral economic relations and highlighting those industries towards which the emphasis in trade and investment is gradually shifting. The question arises: is it possible to return to the indicators of bilateral trade and investment inherent in Russian-Spanish economic relations before the imposition of sanctions? The data on the bilateral trade presented by the Russian and Spanish national statistics differ insignificantly in terms of the total trade turnover but have severe differences at the level of the trade balance. Based on both countries’ statistical databases, the author of the article presents the possible reasons for such discrepancies and considers the general dynamics of the state of foreign trade between Russia and Spain. In addition to stating the negative trends in foreign trade, there are problems in investment cooperation, which until recently was considered one of the “strongholds” of bilateral cooperation under the pressure of sanctions.